Genetic diversity and outcrossing rate of Dipterocarpus dyeri in Ma Da lowland tropical forest (Dong Nai) - Duc, Nguyen Minh; Tam, Nguyen Minh; Duy, Vu Dinh; Xuan, Bui Thi Tuyet; Hien, Dang Phan; Nga, Cao Thi Viet; Nhi, Nguyen Van (Vietnam Journal of Biotechnology, 2018)
Human activities often lead to the disturbed and fragmented habitat and consequently threated species. Dipterocarpus dyeri (Dipterocarpaceae) is widely distributed in lowland rainforests in southeast Vietnam. Due to over- exploitation and habitat destruction in the 1980s and 1990s, the species is listed as threatened. Understanding the genetic variation and mating rate within D. dyeri population that occurs in forest patches is necessary to establish effectively conservation strategies for this species. To conserve the species in tropical forests, genetic diversity and mating rate were investigated on the basis of eight microsatellites (single sequence repeat, SSR). All of the eight loci were polymorphic. A total of 33 different alleles were observed across the screened loci. The SSR data indicated high genetic diversities (NA = 4.1; HO = 0.461 and HE = 0.543) and the inbreeding value was high (0.185). The mating system parameters were determined using the mixed mating model and indicated high outcrossing rates (tm = 0.884 and ts = 0.645). The differences of significant tm - ts value indicated that inbreeding contributed to selfing rate for this species in lowland tropical forests of Ma Da. This study also indicated the importance of conserving the genetic resources of Dipterocarpus dyeri species in Ma Da rainforests. Genetic conservation should derive from correlated outcrossing. The conservation strategy should be established an ex-situ conservation site with new big population for this species from all genetic groups, which might improve its fitness under different environmental stresses.